Walt Whitman's Songs of Male Intimacy and Love : "Live Oak, with Moss" and "Calamus" - Whitman, Walt, 1819-1892 (Iowa Whitman series., 2011)
This volume includes Whitman's handwritten manuscript version of the twelve "Live oak, with moss" poems along side with a print transcription of these poems on the opposite page, followed by a facsimile of the original version of the "Calamus" poems published in the 1860-61 edition of Leaves of grass, and a reprint of the final version of the "Calamus" poems in the 1881 edition of Leaves of grass.